Praktik Cash Waqf Linked Deposit di Wakaf Warrior dalam Tinjauan PP 42/2006 dan PERBWI 01/2020 - Fathin Nur Najmi Laila; Syafaat Muhari (JOURNAL SAINS STUDENT RESEARCH, 2026)
In the digital enocomy era, innovations in cash waqf management have grown rapidly, one of which is teh Cash Waqf Linked Deposit (CWLD) scheme. This scheme integrates cash waqf with Islamic bank deposits, where the returns are utilized for social programs and economic empowerment. One institution implementing CWLD is Wakaf Warrior, a productive waqf movement based on entrepreneurship and volunteerism. Although CWLD has great potential in supporting Islamic financial inclusion, its compliance with existing waqf regulation in Indonesia still requires examination. This study aims to analyze the conformity of CWLD practices in Wakaf Warrior with Government Regulation Number 42 of 2006 and Indonesian Waqf Board Regulation Number 01 of 2020. The research employs a qualitative case study with a normative approach through interviews, observations, and documentation. The findings indicate that CWLD implementation in Wakaf Warrior complies with regulations in term of legal, institutional, and management aspects, through the agreement of three parties, separate account, security of principal funds, dispute resolution mechanisms, and transparent reporting.